A generation later : household strategies and economic change in the rural Philippines - Eder, James F. (University of Hawai'i Press, 1999)
"A Generation Later moves beyond analytical models of rural change that focus on the peasant/agricultural aspect of rural communities and makes a convincing case for an approach that integrates farm and nonfarm occupations and does justice to the conditions of occupational multiplicity that characterize, to an increasing extent, many of the rural communities in Asia. In this context, it challenges conventional (and simplistic) "peasant to proletarian" views of change. Rather than finding a dreary and dispirited landscape of sameness and hardship, it offers some empirical support for amore optimistic view of the region's future, one of growing household prosperity and widespread individual opportunity"--Publisher's description